EU Directive on Work-Life Balance for Parents and Carers in the Context of Human Resources Problems in the Polish Public Administration - Anna Łukaszuk (Review of European and Comparative Law)
This article attempts to present and assess the adequacy of the solutions in the directive on work-life balance for parents and carers in the context of the problems and challenges faced by the Polish public administration in human resource management. The directive’s solutions are analyzed from the perspective of post-pandemic reality, demography, changes in the structure of society and equality, and growing numbers and activation of women in the labor market. An example of applying the WLB policy in the Polish civil service was also presented.